Structure–Activity Relationship Studies of Tetracyclic Pyrrolocarbazoles Inhibiting Heterotetrameric Protein Kinase CK2 - Lukas Kröger; Sebastian Borgert; Miriam Lauwers; Michaela Steinkrüger; Joachim Jose; Markus Pietsch; Bernhard Wünsch (Molecules)
The serine/threonine kinase CK2 (formerly known as casein kinase II) plays a crucial role in various CNS disorders and is highly expressed in various types of cancer. Therefore, inhibiting this key kinase could be promising for the treatment of these diseases. The CK2 holoenzyme is formed by the recruitment of two catalytically active CK2α and/or CK2α′ subunits by a regulatory CK2β dimer. Starting with the lead furocarbazole W16 (4) inhibiting the CK2α/CK2β interaction, analogous pyrrolocarbazoles were prepared and tested for their protein–protein interaction inhibition (PPII). The key step of the synthesis was a multicomponent Levy reaction of 2-(indolyl)acetate 6, benzaldehydes 7, and N-substituted maleimides 8. Targeted modifications were performed by the saponification of the tetracyclic ester 9a, followed by the coupling of the resulting acid 10 with diverse amines. The replacement of the O-atom of the lead furocarbazole 4 by an N-atom in pyrrolocarbazoles retained or even increased the inhibition of the CK2α/CK2β interaction. The large benzyloxazolidinyl moiety of 4 could be replaced by smaller N-substituents without the loss of the PPII. The introduction of larger substituents at the 2-position and/or at p-position of the phenyl moiety at the 10-position to increase the surface for the inhibition of the PPI did not enhance the inhibition of the CK2α/CK2β association. The strong inhibition of the CK2α/CK2β association by the histidine derivative (+)-20a (Ki = 6.1 µM) translated into a high inhibition of the kinase activity of the CK2 holoenzyme (CK2α2β2, IC50 = 2.5 µM). Thus, 20a represents a novel lead compound inhibiting CK2 via the inhibition of the association of the CK2α and Ck2β subunits.